2000
DOI: 10.1021/jm000133v
|View full text |Cite
|
Sign up to set email alerts
|

Nonpeptide αvβ3 Antagonists. 1. Transformation of a Potent, Integrin-Selective αIIbβ3 Antagonist into a Potent αvβ3 Antagonist

Abstract: Modification of the potent fibrinogen receptor (alpha(IIb)beta(3)) antagonist 1 generated compounds with high affinity for the vitronectin receptor alpha(v)beta(3). Sequential modification of the basic N-terminus of 1 led to the identification of the 5,6,7, 8-tetrahydro[1,8]naphthyridine moiety (THN) as a lipophilic, moderately basic N-terminus that provides molecules with excellent potency and selectivity for the integrin receptor alpha(v)beta(3). The THN-containing analogue 5 is a potent inhibitor of bone re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 30 publications
1
54
0
Order By: Relevance
“…data) was synthesized as previously described. Briefly, ITOP was developed from a potent fibrinogen receptor antagonist (3-amino-2(S)-arylsulfonylaminopropionic acid derivative) [20] with further structural modifications, followed by conjugation to FITC. The conjugation of the fluorophore to the integrin antagonist did not alter the binding affinity or selectivity to integrin αvβ3.…”
Section: Methodsmentioning
confidence: 99%
“…data) was synthesized as previously described. Briefly, ITOP was developed from a potent fibrinogen receptor antagonist (3-amino-2(S)-arylsulfonylaminopropionic acid derivative) [20] with further structural modifications, followed by conjugation to FITC. The conjugation of the fluorophore to the integrin antagonist did not alter the binding affinity or selectivity to integrin αvβ3.…”
Section: Methodsmentioning
confidence: 99%
“…11 The 1,8-tetrahydronaphthyridine moiety was incorporated, which was known to be an effective guanidine mimetic when applied to a v b 3 antagonists. 12 Reaction of the hydroxyamidine 1 with 3-substituted or 3,3-disubstituted glutaric anhydrides 2 allowed construction of the 1,2,4-oxadiazole ring with concomitant introduction of a substituted butanoic acid chain (Scheme 1). 13 This allowed for the rapid parallel synthesis of a series of analogs in racemic form.…”
Section: Sc-68448mentioning
confidence: 99%
“…The 1,8-tetrahydronaphthyridine moiety was clearly an effective guanidine mimetic for these oxadiazole based a v b 3 antagonists, which is in line with the findings of other researchers. 12 Some structural variation of this part of the molecule was investigated however to determine if further optimization were possible. A selection of guanidine mimetic variants is shown in Table 3.…”
Section: Sc-68448mentioning
confidence: 99%
“…[15,16] Furthermore, a v b 3 antagonists may have potential use in the suppression of proliferative diabetic retinopathy, which causes blindness in diabetic patients, [17,18] and they may also be useful for the treatment of osteoclast-mediated osteoporosis. [19] It has been demonstrated that blocking of a v b 3 by a synthetic peptide mimetic diminished osteoclastic bone resorption in vitro and in vivo. [20±22] 1,3-bis-tert-butoxycarbonyl-2-methyl-2-thiopseudourea was carried out to obtain derivative 20.…”
Section: Introductionmentioning
confidence: 99%